Biomechanical and muscle performance analysis during functional electrical stimulationevoked cycling in spinal cord injury individuals / Puteri Nur Farhana Hamdan - Puteri Nur Farhana , Hamdan (2024)
Functional electrical stimulation (FES)-evoked cycling has been reported to enhance muscle strength and fatigue resistance after spinal cord injury (SCI). Its goal is to produce the highest possible power to maximize physiological benefits. With the tuning between the foot and pedal contact point to the relative strength of the ankle plantar flexors, power production was simulated to be improved by 14% by releasing the ankle joint from a fixed ankle setup and with the stimulation of the tibialis anterior and triceps surae. FES-evoked cycling however produces very low power and efficiency in individuals with SCI compared to healthy individuals. This is because of the early onset of muscle fatigue among individuals with SCI. To date, muscle fatigue during FESevoked cycling in individuals with SCI has been quantified in many studies by means of peak torque or pedal power output (PO) decrement. These measures may not be sensitive and do not reflect metabolic markers of fatigue. This study aimed to experimentally determine the effect of releasing the ankle joint on the pedal power production during FES-evoked cycling in individuals with SCI. This study also aimed to examine the relationship between the vibrational performance of electrically-evoked muscles measured through mechanomyography (MMG) and its oxidative metabolism through near-infrared spectroscopy (NIRS) characteristics during FES-evoked cycling in individuals with SCI. This study also sought to quantify muscle fatigue during FESevoked cycling using MMG and NIRS. Seven individuals with motor complete SCI participated in this study. In achieving the first objective of this study, all participants performed one minute of fixed-ankle and free-ankle FES-evoked cycling with two stimulation modes. In Mode 1, participants performed FES-evoked cycling with the stimulation of quadriceps and hamstring muscles only (QH stimulation), while Mode 2 had stimulation of quadriceps, hamstring, tibialis anterior, and triceps surae muscles (QHT stimulation). Free-ankle FES-evoked cycling offered greater ankle plantar- and dorsiflexion at specific slices of 20° crank angle intervals compared to fixed-ankle. Fixed-ankle QHT stimulation elevated the peak normalized pedal PO by 14.5% more than free-ankle QH stimulation. Releasing the ankle joint without the stimulation of triceps surae and tibialis anterior reduces PO. The findings of this study suggest that QHT stimulation is necessary during free-ankle FES-evoked cycling to maintain power production as fixed-ankle. For the second and third objectives, all participants performed 30 minutes of FES-evoked cycling with MMG and NIRS sensors on their quadriceps throughout the cycling, and the signals were analyzed. A moderate significant negative correlation was found between MMG root mean square (RMS) and oxyhaemoglobin (O2Hb) [r = -0.38, p = 0.003], and RMS and total haemoglobin (tHb) saturation [r = -0.31, p = 0.017]. There were significant differences in RMS, O2Hb, and tHb saturation during pre- and post-fatigue of FES-evoked cycling (p < 0.05). MMG RMS was negatively associated with O2Hb and muscle oxygen derived from NIRS. MMG and NIRS sensors showed good inter-correlations with each other, suggesting a promising use of MMG for characterizing metabolic fatigue at the muscle oxygenation level during FES-evoked cycling in individuals with SCI.